PENGARUH BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT. VARIA USAHA BETON SIDOARJO - AMINUL WAHIB, MUHAMMAD (Jurnal Ilmu Manajemen (JIM), 2018)
PT. Varia Usaha Beton is a national scale manufacturing company engaged in construction, namely the provision of concrete and building construction service. Since it was first established in 1991, PT. Varia Usaha Beton continues to do business development, which until now has reachted more than 30 plan spread throughtout Indonesia. This company has a vision to become the first custoer choice of concrete company and aggregates in the national market. This study aims to examine and analyze the influence of company culture on employee performance through organizational commitment and Organizational Citizenship Behavior (OCB). This research is causal research and used a quantitative approach. The sampling technique uses saturated samples with 54 respondents. Structural Equation Modeling with SmartPLS software is used as a statistical analysis tool. The results of this study indicate that the company culture have a effect on organizational commitment. Company culture has no effect on organizational commitment. Company culture has an effect on Organizational Citizenship Behavior (OCB). Organizational commitment has no effect employee performance. Organizational Citizenship Behavior (OCB) has no effect on employee performance. Organizational commitment as an intervening variable does not effect the relationship of company culture on employee performance. Organizational Citizenship Behavior (OCB) as an intervening variable does not effect the relationship of company culture on employee performance. Keywords: employee performance; company culture; organizational citizenship behavior (ocb); organizational commitment.